Aspirin use and bleeding risk after endoscopic submucosal dissection in patients with gastric neoplasms - Cho, S-J.; Choi, I. J.; Kim, C. G.; Lee, J. Y.; Nam, B.-H.; Kwak, M. H.; Kim, H. J.; Ryu, K. W.; Lee, J. H.; Kim, Y.-W. (Endoscopy, 2012)
Background and study aim: The risk of bleeding after endoscopic submucosal dissection (ESD) in patients with early gastric neoplasms who do not discontinue aspirin for the procedure has not been established. We aimed to investigate whether post-ESD gastric bleeding is increased in patients who take aspirin.Patients and methods: Patients who underwent ESD for early gastric neoplasms at the National Cancer Center Hospital, Korea, between November 2008 and January 2011 were enrolled. The risk of post-ESD bleeding was evaluated using Poisson regression analysis. Results: We categorized 514 patients into three groups according to aspirin intake at the time of the procedure: patients who never used aspirin (n = 439), patients who interrupted aspirin use for 7 days or more (n = 56), and patients who continuously used aspirin (n = 19). Post-ESD bleeding occurred in 4.1 % (21 /514) overall, and was more frequent in continuous aspirin users (4 /19 [21.1 %]) than in those who never used aspirin (15 /439 [3.4 %]) (P = 0.006) and those with interrupted aspirin use (2 /56 [3.6 %]) (P = 0.033). Multivariate analysis showed that use of aspirin by itself was associated with post-ESD bleeding (relative risk [RR] 4.49; 95 % confidence interval [95 %CI] 1.09 – 18.38). The resumption of clopidogrel combined with aspirin use (RR 26.71, 95 %CI 7.09 – 100.53), and increased iatrogenic ulcer size (RR 1.52, 95 %CI 1.14 – 2.02), were significantly associated with post-ESD bleeding. Conclusions: Continuous aspirin use increases the risk of bleeding after gastric ESD. Aspirin use should be stopped in patients with a low risk for thromboembolic disease to minimize bleeding complications.